AGANT SHEDS STAFF. - Campbell, Lisa (Bookseller, 2013)
The article reports on the decision of Dave Addey, app developer and owner of Agant, to cut his seven member staff, which he said is caused by iOS App Store's set-up that does not support discovery, trailing and long-term life of high-value apps.